Examining Disparities in Religious Court Decisions on Voluntary Itsbat Nikah and Underage Siri Marriages - Hadi Nur Ikhwan; Y. A Triana Ohowaitun; Dominikus Rato (Rechtenstudent, 2024)
This study examines two Religious Court decisions in Indonesia, Case Number 9/Pdt.P/2025/Pa.Ngr and Case Number 23/Pdt.P/2025/Pa.Klp, both concerning applications for marriage validation (itsbat nikah). The two cases share similar characteristics because the marriages were unregistered and the wife was underage at the time of marriage. Although both cases were decided by a single judge, their rulings and legal considerations differ, offering insight into judicial discretion and legal interpretation in voluntary cases. This research uses a normative juridical approach focusing on the analysis of Indonesian positive law, including legislation, judicial decisions, and literature. The study aims to identify the legal basis, reasoning, and implications behind the different judicial outcomes. Findings show that in cases of unregistered marriages, judges may either grant or reject marriage validation requests depending on their interpretation of legal norms and the specific circumstances. These differences may create legal uncertainty and disadvantage parties seeking recognition of their marital status. Therefore, it is important for individuals to comply with the legal marriage age requirement of 19 years to ensure the legality and protection of their marital rights under Indonesian law.